2003
DOI: 10.1016/s0012-1606(03)00097-6
|View full text |Cite
|
Sign up to set email alerts
|

Parp1-deficiency induces differentiation of ES cells into trophoblast derivatives

Abstract: Embryonic stem (ES) cells deficient in the enzyme poly(ADP-ribose) polymerase (Parp1) develop into teratocarcinoma-like tumors when injected subcutaneously into nude mice that contain cells with giant cell-like morphology. We show here that these cells express genes characteristic of trophoblast giant cells and thus belong to the trophectoderm lineage. In addition, Parp1(-/-) tumors contained other trophoblast subtypes as revealed by expression of spongiotrophoblast-specific marker genes. The extent of giant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 35 publications
4
67
0
1
Order By: Relevance
“…As mentioned earlier, OCT4 repression allows CDX2 to promote formation of the trophectoderm lineage (26). Mouse ESC lacking poly (ADP-ribose) polymerase expression show enhanced spontaneous differentiation of trophoblast giant cells (75). Recently, it has also been reported that collagen type IV, a basement membrane constituent, can direct differentiation of mouse ESC toward the trophectoderm lineage (76).…”
Section: A Spontaneous Differentiation Of Esc To Trophoblastsmentioning
confidence: 86%
“…As mentioned earlier, OCT4 repression allows CDX2 to promote formation of the trophectoderm lineage (26). Mouse ESC lacking poly (ADP-ribose) polymerase expression show enhanced spontaneous differentiation of trophoblast giant cells (75). Recently, it has also been reported that collagen type IV, a basement membrane constituent, can direct differentiation of mouse ESC toward the trophectoderm lineage (76).…”
Section: A Spontaneous Differentiation Of Esc To Trophoblastsmentioning
confidence: 86%
“…Parp1 -/-ES cells differentiate into trophoblast derivatives in vitro and in ES cell-derived tumors (Hemberger et al, 2003;Nozaki et al, 2013;Nozaki et al, 1999;Ogino et al, 2007). Significant upregulation of H19 in Parp1 -/-ES was detected by a microarray analysis and was then validated by RT-PCR (Ogino et al, 2007).…”
Section: Cell Fate Restriction In Embryonic Cell Lineage By Dna Methymentioning
confidence: 92%
“…They require LIF/STAT3 signaling for maintenance of pluripotency (Hall, Guo et al 2009), while BMP4 provides additional support for self renewal and resistance to differentiation (Ying, Nichols et al 2003). However, mESC are generally recognized as being pluripotent rather than totipotent and only capable of contributing to the embryonic lineage and not to elements of extraembryonic tissues derived from trophectoderm (TE) (Beddington and Robertson 1989;Nagy, Gocza et al 1990), presumably because they are already stably committed offshoots of the ICM and/or its derivative, the epiblast (Rossant and Spence 1998;Hemberger, Nozaki et al 2003). ESC established from monkey and human blastocysts (Thomson, Kalishman et al 1995;Thomson, Itskovitz-Eldor et al 1998), have markedly different characteristics to mESC.…”
Section: Embryonic Stem Cells (Esc) and Trophoblast Stem Cells (Tsc)mentioning
confidence: 99%